RFRP neurons are critical gatekeepers for the photoperiodic control of reproduction - Simonneaux, Valerie; Ancel, Caroline (Frontiers in Endocrinology, 2012)
Seasonally-breeding mammals rely on the photoperiodic signal to restrict their fertility to a certain time of the year. The photoperiodic information is translated in the brain via the pineal hormone melatonin, and it is now well established that it is the variation in the duration of the nocturnal peak of melatonin which synchronises reproduction with the seasons. The Syrian hamster is a long day breeder, and sexual activity is therefore promoted by exposure to a long day photoperiod and inhibited by exposure to a short day photoperiod. Interestingly, in this species electrolytic lesion of the mediobasal hypothalamus abolishes the short day-induced gonadal regression. We have shown that the expression of a recently discovered neuronal population, namely RFamide-related peptide (rfrp) neurons, present in the mediobasal hypothalamus, is strongly down-regulated by melatonin in short day conditions, but not altered by circulating levels of sex steroids. The role of rfrp and its product RFRP-3 in the regulation of reproductive activity has been extensively studied in mammals, and our recent findings indicate that this peptide is a potent stimulator of the reproductive axis in the Syrian hamster. It induces a marked increase in GnRH neuron activity and gonadotrophin secretion, and it is able to rescue reproductive activity in short day sexually inactive hamsters. Little is known about the localisation of the RFRP-3 receptor, GPR147, in the rodent brain. Accumulating evidence suggests that RFRP-3 could be acting via two intermediates, the GnRH neurons in the preoptic area and the Kiss1 neurons in the arcuate nucleus, but future studies should aim at describing the localisation of Gpr147 in the Syrian hamster brain. Altogether our data indicate that the rfrp neuronal population within the mediobasal hypothalamus might be a serious candidate in mediating the photoperiodic effects of melatonin on the regulation of the reproductive axis.